Reflections on gravitational waves: what I learned in the Iniciação Científica Júnior - Poloni, Ana Júlia De Paula; Santana, Wanessa Santos; Barcellos, Leandro da Silva (Cadernos de Astronomia, 2023)
We show part of the work developed in Junior Scientific Initiation and Mostra de Astronomia do Espírito Santo. This article aims to disseminate those topics for the public. We realized a bibliographical survey about Gravitational Waves, the progress of technological artifacts to detection and analyze those waves and the participation of Brazilian scientists in that context. For that, we consult de data of Caderno de Astronomia, Revista Brasileira de Ensino de Física and Revista Exame. We hope this text awaken the interest and curiosity of the public.
Keywords: Astronomy; Gravitational Waves; gravitation